(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Counseling on safe and effective use of drugs for outpatients plays an important role in the treatment process. The study aims to evaluate the current status of drug counseling and the possibility of applying telepharmacy (remote pharmaceutical care) at Le Van Viet Hospital, Ho Chi Minh city. Subjects and methods: A cross-sectional descriptive study to investigate the current status of drug counseling at Le Van Viet Hospital, Ho Chi Minh city by surveying 400 outpatients aged 18 years and older and representatives of the Board of Directors, leaders and pharmacists of the hospital’s Pharmacy Department from November 2023 to March 2024. Results: 46.5% of the survey respondents wanted medication consultation; 39.6% of the survey respondents wanted to receive online medication consultation if the hospital implemented the service. 100% of pharmacists and hospital management believed that remote medication consultation via the telepharmacy system could be a solution to address patients’ consultation needs and the current facilities of the hospital. Conlusion: At Le Van Viet Hospital, medication consultation is limited due to patients’ awareness, infrastructure, and human resources. It is necessary to raise patients’ awareness about the importance of medication consultation. Telepharmacy could improve the quality of care and has promising prospects for expansion due to positive reception from both patients and the hospital.